2007
DOI: 10.1364/ao.46.005368
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peristrophic multiplexing and a combination of angular and peristrophic holographic multiplexing in a thick PVA/acrylamide photopolymer for data storage

Abstract: Two different types of multiplexing are used to store 90 holograms at the same location in a polyvinyl alcoholacrylamide photopolymer material. In the first, the 90 holograms are stored using only peristrophic multiplexing, whereas in the second a combination of angular and peristrophic multiplexing is used. The results (diffraction efficiency and dynamic range, M#) obtained with these two multiplexing techniques are compared. With the first, the dynamic range was M# ϭ 13 and with the second M# ϭ 8. An exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 17 publications
1
45
0
Order By: Relevance
“…These objects were stored at the same position in the material using peristrophic multiplexing because previous papers showed that when a not very large number of holograms (fewer than 200) are stored, higher diffraction efficiency is obtained with peristrophic multiplexing [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These objects were stored at the same position in the material using peristrophic multiplexing because previous papers showed that when a not very large number of holograms (fewer than 200) are stored, higher diffraction efficiency is obtained with peristrophic multiplexing [25].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they were stored with a beam ratio of 100 and reconstructed on the CCD with a reading beam intensity of 0.03mW/cm 2 [24]. As the holograms are stored in the material, the dynamic range is consumed [21][22][23]25]; therefore, the exposure must be increased in order to store more holograms. Of course, when all the dynamic range is consumed, no more holograms will be formed in the material even if the exposure is increased.…”
Section: B Thickness Of 80 µMmentioning
confidence: 99%
“…Rise time was small (0.28-0.34 ms) while the decay time decreased along RS (1.92)> MS (1.82)>VTMS (1.28 ms). The additives which are interposed at the polymer-LC interfaces not only decrease the surface anchoring but also influence the orientation of LC droplet directions [25]. It seems that VTMS is a preferred interface modifier among the three.…”
Section: Response Timementioning
confidence: 99%
“…where η i is the maximum DE of each of the gratings recorded, and the sum is over the M holographic gratings multiplexed in one location [17]. The photopolymer layer with 130 μm thickness was found to have an M# of 1.7.…”
Section: Peristrophic Multiplexingmentioning
confidence: 99%
“…This type of multiplexing has the added advantage that it can be combined with other multiplexing methods to increase the storage density of holographic storage systems [16]. In the present work, an exposure-scheduling method was used to exploit the entire dynamic range [17] of the material and to record equal strength holographic gratings in it. The dynamic range that is a measure of the storage capacity of the material was determined by calculating the M number (M#) [18].…”
Section: Introductionmentioning
confidence: 99%